2008
DOI: 10.1016/j.lfs.2008.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitors and raft inhibitors shorten the period of Period1-driven circadian bioluminescence rhythms in rat-1 fibroblasts

Abstract: Alterations in circadian rhythm generation may be related to the development of mood disorders. Although it has been reported that the most popular antidepressant, selective serotonin reuptake inhibitors (SSRIs) affect circadian phase, no data are available that describe the effects of SSRIs on other circadian parameters (period, amplitude and damping rate) in dissociated cells. In the present study we used real-time monitoring of bioluminescence in rat-1 fibroblasts expressing the Period1-luciferase transgene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
(57 reference statements)
0
23
0
Order By: Relevance
“…Different selective serotonin reuptake inhibitors were found to significantly shorten circadian period in SCN and accelerate damping rate in fibroblasts [101]. In rodents, fluoxetine was shown to advance SCN phase [102] and to modulate both serotonin and lightinduced phase shifts [103,104].…”
Section: Antidepressant Drugsmentioning
confidence: 99%
“…Different selective serotonin reuptake inhibitors were found to significantly shorten circadian period in SCN and accelerate damping rate in fibroblasts [101]. In rodents, fluoxetine was shown to advance SCN phase [102] and to modulate both serotonin and lightinduced phase shifts [103,104].…”
Section: Antidepressant Drugsmentioning
confidence: 99%
“…Investigators have suggested that neurotransmitter signaling may occur via clustering of receptors in lipid rafts or caveolae, and the effects of lipid rafts on neurotransmitter signaling have been implicated in neurological and psychiatric diseases in general (Nomura et al , 2008, Pani and Singh, 2009), and in mood disorders in particular (Brambilla et al , 2003, Shiah and Yatham, 2000, Donati et al , 2008). Traditionally, the brain systems receiving the greatest attention in neurobiological studies of mood disorders were the monoaminergic neurotransmitter systems (e.g., the serotonergic, dopaminergic, and norepinephrinergic systems) that are extensively distributed throughout the network of limbic, striatal, hippocampal, and prefrontal cortical neuronal circuits (Drevets, 2000, Manji and Duman, 2001, Nestler et al , 2002).…”
Section: Stress and Sleep Deprivation Cause Oxidative Damage To Mitocmentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors affect circadian phase (Nomura et al, 2008). Serotoninergic cell bodies appear in the suprachiasmatic nuclei of hamsters that have been held in constant darkness, while serotonergic cells are absent in the suprachiasmatic nuclei of animals that have been bilaterally enucleated (Yamazaki et al, 1999).…”
Section: Discussionmentioning
confidence: 99%